Synthesis and radiofluorination of novel fluoren-9-one based derivatives for the imaging of α7 nicotinic acetylcholine receptor with PET. Issue 9 (15th May 2018) - Teodoro, Rodrigo; Scheunemann, Matthias; Wenzel, Barbara; Peters, Dan; Deuther-Conrad, Winnie; Brust, Peter
Graphical abstract: Abstract: By structure–activity relationship studies on the tilorone scaffold, the 'one armed' substituted dibenzothiophenes and the fluoren-9-ones were identified as the most potential α7 nAChR ligands. While the suitability of dibenzothiophene derivatives as PET tracers is recognized, the potential of fluoren-9-ones is insufficiently investigated. We herein report on a series of fluoren-9-one based derivatives targeting α7 nAChR with compounds 8a and 8c possessing the highest affinity and selectivity. Accordingly, with [ 18 F]8a and [ 18 F]8c we designed and initially evaluated the first fluoren-9-one derived α7 nAChR selective PET ligands. A future application of these radioligands is facilitated by the herein presented successful implementation of fully automated radiosynthesis.